New European Perspectives - Brexit: The End of a New Beginning: Array - Petcu, Diana Maria (Acta Universitatis Danubius. Relationes Internationales, 2021)
Since the establishment of the ECSC (European Coal and Steel Community in 1951) to the present day, the European Union has not faced such a situation, leaving a Member State in the European sphere, which is why Brexit is a new phenomenon. I can say that it is a new project, and we can see that it is a new process, that of disintegration, in which a state no longer wants to be part of the EU, on the contrary, it wants to leave the European circle. It is intended to be ordered by various separation provisions in order to prevent disruption and to provide legal certainty to the citizens of the European Union and the United Kingdom.